Assessment of shelf sea tides and tidal mixing fronts in a global ocean model. (April 2019) - Timko, Patrick G.; Arbic, Brian K.; Hyder, Patrick; Richman, James G.; Zamudio, Luis; O'Dea, Enda; Wallcraft, Alan J.; Shriver, Jay F.
Abstract: Tidal mixing fronts, which represent boundaries between stratified and tidally mixed waters, are locations of enhanced biological activity. They occur in summer shelf seas when, in the presence of strong tidal currents, mixing due to bottom friction balances buoyancy production due to seasonal heat flux. In this paper we examine the occurrence and fidelity of tidal mixing fronts in shelf seas generated within a global 3-dimensional simulation of the HYbrid Coordinate Ocean Model (HYCOM) that is simultaneously forced by atmospheric fields and the astronomical tidal potential. We perform a first order assessment of shelf sea tides in global HYCOM through comparison of sea surface temperature, sea surface tidal elevations, and tidal currents with observations. HYCOM was tuned to minimize errors in M2 sea surface heights in deep water. Over the global coastal and shelf seas (depths <200 m) the area-weighted root mean square error of the M2 sea surface amplitude in HYCOM represents 35% of the 50 cm root mean squared M2 sea surface amplitude when compared to satellite constrained models TPXO8 and FES2014. HYCOM and the altimeter constrained tidal models TPXO8 and FES2014 exhibit similar skill in reproducing barotropic tidal currents estimated from in-situ current meter observations. Through comparison of a global HYCOM simulation with tidal forcing to a global HYCOM simulation with no tides, and also to previous regional studies of tidal mixing fronts in shelf seas, we demonstrate that HYCOM with embedded tides exhibits quite high skill in reproducing known tidal mixing fronts in shelf seas. Our results indicate that the amount of variability in the location of the tidal mixing fronts in HYCOM, estimated using the Simpson-Hunter parameter, is consistent with previous studies when the differences in the net downward heat flux, on a global scale, are taken into account. We also provide evidence of tidal mixing fronts on the North West Australian Shelf for which we have been unable to find references in the existing scientific literature. Highlights: We perform a first order assessment of the skill of HYCOM tides in the coastal and shelf seas. RMSE for tidal heights represents 23–35% of the RMS amplitude in the coastal and shelf seas of global HYCOM. Inclusion of tides in global HYCOM has a visible impact on SST in coastal and shelf seas. HYCOM with embedded tides reproduces known seasonal tidal mixing fronts in their expected location. We provide evidence for the existence of tidal mixing fronts on the North West Australian Shelf.